Comparison of isometric and isokinetic knee muscles strength between elite, sub elite and amateur Iranian young soccer players - parisa namazi; mostafa zarei; fariborz hovanloo; mohammad hadi ghasemi (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: Muscle strength is needed to perform many movements and skills in football such as speed decreasing, shooting, dribbling, rotating, and jumping. Several studies shown that lower limb muscle strength can increase the quality of exercise skills. But, few studies have compared the strength of players at different levels. Therefore, the present study intends to investigate the strength of the isokinetic and isometric knee muscles of the elite, sub-elite and amateur football players of Iran. Methods: The isokinetic strength of the knee muscles in 102 soccer players including 29 players of the national under-23 football team of Iran (elite), 29 players of 1st division of under-23 football team of Iran (sub-elite) and 44 players of 2nd division of under-23 football team of Tehran province (amateur) was measured for angular momentum of 60 and 180 degrees per second by the isokinetic Biodex. The isometric strength of flexor and extensor muscles of knee were measured at an angle of 60 degree. Results: The results of the ANOVA test showed that elite player had superior strength of flexor and extensor knee muscles in both momentum angles of 60 and 180 degrees per second and flexor/ extensor isokinetic strength ratio at 180 degrees per second speed than sub-elite and amateur players significantly. However, there was no significant difference in the ratio of flexor/ extensor isokinetic strength ratio at 60 degrees per second. Conclusions: Considering the results of the present study, it can be concluded that competition level affect the isokinetic and isometric strength of the knee muscles of young football players of Iran.